Identifying Contractorsâ Planned Quality Costs in Indonesian Construction Projects - Marzuki, Puti F.; Wisridani, M. (Journal of Engineering and Technological Sciences, 2014)
InÂ  a very competitive construction industry, quality costs have to be measuredÂ  toÂ  beÂ  ableÂ  toÂ  identifyÂ  potentialÂ  qualityÂ  problemÂ  areasÂ  andÂ  toÂ  focus attentionÂ  onÂ  workÂ  outputÂ  improvementÂ  opportunities.Â  TheÂ  awarenessÂ  of contractors on the importance of quality costs could be reflected in the extent of theirÂ  qualityÂ  costsÂ  planning.Â  ThisÂ  paperÂ  presentsÂ  anÂ  identificationÂ  ofÂ  planned qualityÂ  costsÂ  inÂ  threeÂ  constructionÂ  projectsÂ  executedÂ  byÂ  twoÂ  largeÂ  Indonesian contractors,Â  aÂ  state-ownedÂ  companyÂ  andÂ  aÂ  privateÂ  companyÂ  inÂ  Jakarta.Â  The objective is to enable the contractors to elaborate their quality costs planning and thereby improve their work output based on the findi ngs. QualityÂ  costsÂ  areÂ  first grouped intoÂ  threeÂ  categories: prevention, appraisal,Â  andÂ  failureÂ  costs.Â  Based on theÂ  worksÂ  ofÂ  previousÂ  researchers,Â  aÂ  listÂ  ofÂ  qualityÂ  managementÂ  activitiesÂ  that should be covered in each quality costs category is then created. The contractorsâ planned quality costs dataÂ  for each category areÂ  identified andÂ  collected through interviewsÂ  andÂ  questionnaireÂ  surveysÂ  thatÂ Â  referÂ  toÂ  theÂ  list.Â  QualityÂ  costsÂ  are expressedÂ  asÂ  aÂ  percentageÂ  ofÂ  contractÂ  value.Â  ItÂ  isÂ  revealedÂ  thatÂ  althoughÂ  large contractorsÂ  alreadyÂ  haveÂ  certainÂ  knowledgeÂ  onÂ  qualityÂ  costsÂ  inÂ  construction projects,Â  these costs areÂ  not planned in a structured wayÂ  through an analysis of systematicÂ  qualityÂ  costsÂ  records.Â  ThroughÂ  costÂ  categorizationÂ  itÂ  isÂ  alsoÂ  shown that higher prevention and appraisal costs lead to lower failure costs.Â  It is then concludedÂ  thatÂ  aÂ  lotÂ  ofÂ  workÂ  isÂ  stillÂ  toÂ  beÂ  doneÂ  byÂ  theÂ  contractorsÂ  toÂ  setÂ  upÂ  a qualityÂ  costsÂ  recordingÂ  systemÂ  whichÂ  canÂ  serveÂ  asÂ  aÂ  basisÂ  forÂ  theirÂ  quality improvement planning.